Parce que j'étais peintre l'art rescapé des camps nazis - Cognet, Christophe 1966-; Breschand, Jean; Moreau, Pierre-François; Kosal, Nara Keo (Jour2Fête, 2014)
"An unprecedented investigation into the artworks created secretly in Nazi concentration and death camps. It converses with the rare handful of living artists who survived the camps and with their curators: about the emotions the works stir, their marginalization, their signature or anonymity, their style, as well as the representation of horror and extermination. But more importantly, perhaps, the film takes a long look at the drawings, wash drawings and paintings held in collections in France, Germany, Israel, Poland, the Czech Republic, Belgium and Switzerland. Director's statement 'I hardly dare to say it, but for a painter, the beauty of it was incredible. It was absolutely vital to reproduce it, to represent and to show it, in order to preserve it for the future', wrote Zoran Music, a survivor of Dachau. The film moves between these fragments of clandestine images and the vestiges of the camps, offering a sensitive search of faces, bodies and landscapes to explore the very notion of artwork and confront the idea of beauty head-on. The stakes are disconcerting, but perhaps it may help us to truly imagine what the camps must have been like, and to feel the respect due an artist, no matter how small or fragile his gesture of drawing." [amazon.co.uk
Original: Frankreich, Deutschland, Polen, Israel 2013
Suppléments: Quand nos veux sont fermés, l'art clandestin à Buchenwald, un film de Christophe Cognet (documentaire, 54 min) ; interview de Christophe Cognet par universciné ; livret: texte de Cyril Neyrat, liste des artistes, noms des intervenants, biographies ; bande-annonce
Bildformat 16:9
Keywords: Geschichte 1938-1945; Kunstproduktion; Kulturleben; Konzentrationslager; Deutschland; Film; DVD-Video